Melatihkan Keterampilan Proses Sains Siswa SMP melalui Aktivitas Laboratorium Berbasis Kimia Hijau - Ismawati, Riva; Rahayu, Rina (Universitas Pahlawan Tuanku Tambusai, 2025)
It is important for students to master scientific process skills because they help them understand laws, principles and theories through the scientific process. Practicums that pay attention to the principles of green chemistry as one of the activities in the laboratory need to be carried out to support students' mastery of science process skills. Several related problems have been identified, namely science teachers and students do not know the principles of green chemistry, there is no training related to science practicum based on green chemistry principles, science teachers rarely provide learning experiences in the form of practical activities in the laboratory, junior high school students' science process skills are still low. The aim of implementing the service is to provide knowledge about green chemistry principles, improve science process skills, provide science practicum experience based on green chemistry principles. Service activities are carried out using discussion, problem study and practice methods. The results obtained were that participants had mastered the knowledge of green chemistry principles and science process skills in the high category. These results show the success and importance of the service carried out to increase the participants' knowledge and skills.